Numerical Compensation of Air Absorption of Sound in Scale Model Measurements - ĆIRIĆ, Dejan G.; PANTIĆ, Aleksandar (Archives of Acoustics, 2012)
The absorption of sound in air represents one of the main problems of the scale model measurements. This absorption, especially at higher frequencies, is considerably greater than the value determined by the law of acoustical similarity between the full scale and the scale model. Different alternatives are applied for compensation of the excess air absorption including a numerical compensation. In this paper, a modified approach to numerical compensation is proposed. It is based on compensation of the sound decay only, and not background noise. As a consequence, there is no an increase of background noise in the compensated impulse response. The results obtained by the proposed procedure are compared to the corresponding ones obtained by the other procedures.